Blockchain-based architecture centred patient for decentralised storage and secure sharing health data. (14th March 2022) - Zarour, Karim; Bounab, Oussama Abdelilleh; Marir, Yassmine; Boumezbeur, Insaf
The healthcare sector has seen data-sharing systems emerge between patients and different healthcare providers. These systems have provided an excellent service to this sector and have positively contributed to scientific research and medical diagnosis. On the other hand, data security issues have arisen. Besides, traditional centralised storage methods pose a significant threat to this information's survival, which continues to increase with the emergence of portable devices. This work proposes an architecture that combines revolutionary technologies: Blockchain and the interplanetary file system (IPFS) to secure sharing and decentralised healthcare data storage.